2013
DOI: 10.1038/bjc.2013.400
|View full text |Cite
|
Sign up to set email alerts
|

A randomised, placebo-controlled, double-blind study of aprepitant in nondrinking women younger than 70 years receiving moderately emetogenic chemotherapy

Abstract: Background:We evaluated the efficacy of aprepitant plus granisetron and an increased dose of dexamethasone in selected patients undergoing moderately emetogenic chemotherapy (MEC).Methods:Nondrinking women <70 years undergoing MEC were randomly assigned to aprepitant (day 1, 125 mg; days 2 and 3, 80 mg) or placebo. Dexamethasone on days 1–3 was 12, 4, and 4 mg with aprepitant and 20, 8, and 8 mg with placebo. The primary end point was complete response (CR; no emesis or rescue therapy) during 120 h of the firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
67
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 26 publications
1
67
0
Order By: Relevance
“…The addition of aprepitant to standard antiemetic regimens yielded absolute benefits of 14% for the measure of no emesis in the overall phase16, 19 and for the CR rate in the overall phase20 in carboplatin‐treated patients. Smaller studies have produced inconsistent results for the benefit of aprepitant in patients administered carboplatin therapy 21, 22, 23. Data on netupitant also suggest a similar benefit based on measures of no emesis and CR in the overall phase with historical controls used for comparison 17, 24.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of aprepitant to standard antiemetic regimens yielded absolute benefits of 14% for the measure of no emesis in the overall phase16, 19 and for the CR rate in the overall phase20 in carboplatin‐treated patients. Smaller studies have produced inconsistent results for the benefit of aprepitant in patients administered carboplatin therapy 21, 22, 23. Data on netupitant also suggest a similar benefit based on measures of no emesis and CR in the overall phase with historical controls used for comparison 17, 24.…”
Section: Discussionmentioning
confidence: 99%
“…The aprepitant group showed a better overall CR of 80.3% compared with that of 67.2% for the control group. Tanioka et al (2013) reported on a randomized study of aprepitant in women receiving MEC comprising mainly a carboplatin-or irinotecan-containing regimen. Prevalence of a CR overall was superior, but not significantly higher, in the aprepitant, granisetron and dexamethasone group than in the placebo, granisetron and dexamethasone group (aprepitant group, 62.2%; placebo group, 52.1%).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that combinations of new drugs such as palonosetron (serotonin receptor antagonist of the second generation) and aprepitant (NK-1 receptor antagonist) can offer a better protection. (10,11,15) Apart from drugs, complementary medicines and integrative practices can be associated with treatment such as herbal medicines, homeopathy, acupuncture, relaxation, aromatherapy and others. It is noteworthy that in addition to having these services provided, patients should be counseled regarding their effectiveness and encouraged to carry them out.…”
Section: Discussionmentioning
confidence: 99%